Stalking Nabokov : selected essays - Boyd, Brian, 1952- (Columbia University Press, 2011)
"At the age of twenty-one, Brian Boyd wrote an essay on Vladimir Nabokov that the author called 'brilliant.' After gaining exclusive access to the writer's archives, he wrote a two-part, award-winning biography, Vladimir Nabokov: The Russian Years (1990) and Vladimir Nabokov: The American Years (1991). This collection features essays written by Boyd after completing Nabokov's biography, incorporating material he gleaned from his research as well as new discoveries and formulations."--Provided by publisher.